Health literacy of hypertensive patients and related factors: A cross sectional study - Samira Vazifeh; Nasrin Jafari; Soudabeh Mehdizadeh; Farzaneh Ahmadi (Payesh, 2023)
Objective(s): Health literacy is the capacity of people to acquire, process and understand basic health information and services needed for health decisions. Considering the importance of health literacy, especially in people with underlying and chronic diseases, this study aimed to investigate the health literacy and related factors in hypertensive patients. Methods: This was a cross-sectional study conducted on a sample of hypertensive patients aged 18-65 years attending comprehensive urban health centers in Zanjan, Iran, in 2022. The sampling method was a two-stage cluster with systematic random sampling in each cluster. In order to collect data, the demographic information form and the Health Literacy Instrument for Adults (HELIA) was used. The data were analyzed using descriptive statistics. Results: In all 277 patients entered into the study. The mean age of participants was 55.23 ± 6.75. Most participants (59.6%) were women and married (94.4%), housewives (52%), and 49.5% had inadequate and problematic health literacy score. There was a statistically significant difference between the mean score of health literacy among educated people and illiterate people (p<0.001). Also, there was a statistically significant difference between the mean score of health literacy among people who had sufficient income and those who had insufficient income (p=0.017). People who were regularly under the supervision of a physician had higher health literacy(p=0.033). Conclusion: Considering the undesirable condition of health literacy in hypertensive patients, it is suggested to implement interventions to improve health literacy among this population.